Patients’ needs in asthma treatment: development and initial validation of the NEAT questionnaire - Loerbroks, Adrian; Leucht, Verena; Keuneke, Susanne; Apfelbacher, Christian; Sheikh, Aziz; Angerer, Peter (Journal of asthma, 2016)
Objective: We aimed to develop and tentatively validate an instrument assessing patients’ needs related to asthma treatment. Methods: Patients were recruited through various approaches (e.g. physicians, pharmacies and patient organizations). Utilizing a mixed methods design, we first conducted five focus groups to explore needs among patients. Next, we devised an item pool which was revised, reduced and evaluated by patients. Finally, data from a survey (n = 362) were used to further reduce the item pool and to examine the questionnaire’s psychometric properties and validity. Results: Four broad needs categories emerged from the focus groups: (1) information needs; (2) consideration of patient views in diagnosis; (3) consideration of patient views in treatment planning; and (4) addressing patients’ fears. We devised 45 items, which were reduced to 22 items based on patient feedback. The survey data suggested a 13-item scale with four subscales (“patient expertise”, “drug effects”, “handling drugs” and “exacerbations”). Cronbach’s alpha was acceptable for those subscales (>0.7) and for the total score (0.9). Increasing scores on subscales and the total score (implying more unmet needs) showed close and consistent associations with poor asthma control, reduced quality of life and low treatment satisfaction. Conclusions: The development process of the Needs in Asthma Treatment (NEAT) questionnaire ensured that needs of asthma patient are captured with high validity. The NEAT questionnaire has been shown to be valid, thereby representing a promising tool for research and delivery of patient-centered care.
Gesehen am 12.02.2019